1993
DOI: 10.1172/jci116587
|View full text |Cite
|
Sign up to set email alerts
|

Transient elevations of cytosolic free calcium retard subsequent apoptosis in neutrophils in vitro.

Abstract: Elevation of cytosolic calcium (ICa2+I;) has been reported to induce apoptosis in a number of cell types. However, in the neutrophil, which undergoes apoptosis constitutively during aging in vitro, activation by inflammatory mediators elevates ICa2Ji; and prolongs lifespan via inhibition of apoptosis. To examine this paradox, we investigated the effects of modulation of [Ca2" I upon apoptosis of neutrophils in vitro. Calcium ionophores (A23187, ionomycin) retarded apoptosis in neutrophil populations after 20 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
2

Year Published

1995
1995
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(87 citation statements)
references
References 37 publications
3
82
2
Order By: Relevance
“…Furthermore, intracellular calcium does not appear to be elevated in cells undergoing apoptosis in a number of models (Table I and see Ref. 28) and may appear only as a late consequence of the apoptotic process (18). Indeed, elevated intracellular calcium can inhibit apoptosis in neutrophils (24). Here, we show that the appearance of PS in the outer leaflet is totally inhibited in the absence of extracellular calcium and can be dissociated from the other events of apoptosis, namely DNA degradation and loss of the aminophospholipid translocase activity.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Furthermore, intracellular calcium does not appear to be elevated in cells undergoing apoptosis in a number of models (Table I and see Ref. 28) and may appear only as a late consequence of the apoptotic process (18). Indeed, elevated intracellular calcium can inhibit apoptosis in neutrophils (24). Here, we show that the appearance of PS in the outer leaflet is totally inhibited in the absence of extracellular calcium and can be dissociated from the other events of apoptosis, namely DNA degradation and loss of the aminophospholipid translocase activity.…”
Section: Discussionmentioning
confidence: 59%
“…Although elevation of intracellular calcium has been shown to cause apoptosis in HL-60s (22,23), it has been shown to inhibit apoptosis of neutrophils (24). Thus it was necessary to determine intracellular calcium concentration during apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…As noted above, A23187 treatment delays apoptosis in PMN [5]. However, PMN exposed to Ca 2烯 ionophores increase their [free Ca] by both influx of Ca 2烯 and release of Ca 2烯 from internal stores, and it is unclear whether one, the other, or both of these mechanisms are necessary for the apoptosis-sparing effect.…”
Section: Discussionmentioning
confidence: 97%
“…PMN spontaneously undergo apoptosis when stored in vitro or exposure to CHX or anti-Fas antibody can be used to induce apoptosis rapidly. Previous studies have suggested that intracellular Ca 2烯 balance can modulate this process, as a rise in [free Ca] caused by the Ca 2烯 ionophore A23187 early in storage delays development of apoptosis [5]. Based on this report, we sought to better understand the ionic events associated with apoptosis by determining whether PMN apoptosis induced by CHX resulted in changes in [free Ca] and/or resting .…”
Section: Discussionmentioning
confidence: 99%
“…When neutrophils die by apoptosis they retain their granule contents but lose chemotactic and secretory responsiveness [8] and thereafter are recognised and phagocytosed intact by macrophages [9] which fail to release pro-inflammatory mediators in response to this interaction [10]. Although neutrophils un-*Corresponding author.…”
Section: Introductionmentioning
confidence: 99%